Acute diffuse thyroid swelling after fine‐needle aspiration: A case report and review of the literature. Issue 7 (28th April 2021) - Imaoka, Kouki; Nishihara, Masahiro; Nambu, Junko; Yamaguchi, Megumi; Kawasaki, Yukari; Sugino, Keizo
Abstract: Fine‐needle aspiration (FNA) is the first‐line and a cost‐effective examination method of nonfunctional thyroid nodules. Acute transient thyroid swelling after an FNA is a rare complication, and to date, only 14 cases have been reported in the English literature. Herein, we report a case of a 26‐year‐old woman with acute transient thyroid swelling, which occurred after an ultrasound‐guided FNA of a thyroid nodule. Although the patient had undergone an FNA without complication 2 years previously, the second FNA caused acute thyroid swelling. The present case emphasizes the potential risk of acute thyroid swelling associated with every FNA procedure.